2019
DOI: 10.1177/1359105319833744
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review examining the association between female body image and the intention, initiation and duration of post-partum infant feeding methods (breastfeeding vs bottle-feeding)

Abstract: A systematic review was conducted to examine female body image in relation to the intention, initiation and duration of post-partum infant feeding methods. A search of 10 databases was conducted to identify studies. A total of nine studies were included in the systematic review. All studies were of a non-randomised control design with a total of 13,046 participants. Findings suggest that exclusive breastfeeding is more likely in pregnant women with a higher body image, while those with body concerns had less i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
24
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 37 publications
(25 citation statements)
references
References 43 publications
0
24
0
1
Order By: Relevance
“…A number of studies showed similar findings; women with positive body image with higher body satisfaction and who are less concerned with their shape and weight during postpartum are more likely to initiate breastfeeding and maintain it for a longer duration. 17,18,26,27 For example, a study by Brown et al, 26 followed 128 pregnant women in the United Kingdom for 6 months, found that higher body image concerns during pregnancy and after delivery were associated both with an intention to use and actual use of baby formula starting at birth and with shorter breastfeeding duration.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…A number of studies showed similar findings; women with positive body image with higher body satisfaction and who are less concerned with their shape and weight during postpartum are more likely to initiate breastfeeding and maintain it for a longer duration. 17,18,26,27 For example, a study by Brown et al, 26 followed 128 pregnant women in the United Kingdom for 6 months, found that higher body image concerns during pregnancy and after delivery were associated both with an intention to use and actual use of baby formula starting at birth and with shorter breastfeeding duration.…”
Section: Discussionmentioning
confidence: 99%
“…According to seven out of nine peer-reviewed studies identified in a systematic review study, 18 women with body concerns for weight, shape, and the perception of feeling fat influenced on their decision on which infant feeding methods to choose during pregnancy (i.e., intention to breastfeed), after delivery (i.e., breastfeeding initiation), and during postpartum, (i.e., breastfeeding duration). Mothers who expressed a more positive perception of their body were more likely to breastfeed and continue with it for a longer duration.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations